Analysis of the current legal status of land use - Kharytonenko, R.; Kolisnyk, G. (Land Management, Cadastre and Land Monitoring, 2020)
The analysis of the state of land use on the example of institutions and enterprises of the National Academy of Agrarian Sciences of Ukraine in the context of studying the compliance of the State Land Cadastre (SLC), the State Register of Real Rights (SRRR) and title documents on land use rights. The necessity of conducting analysis and making managerial decisions as a supplement to the land inventory or a separate management to solve problems that are not solved by developing land management documentation (technical inventory documentation) is substantiated. Problems in the legal status, which were identified with the help of data from the SLC, SRRR, as well as the source information of the title documents, are highlighted. It is proposed to divide them into typical, which are inherent in the majority of land uses of NAAS and exceptional, which have not become widespread. The classification of the revealed problems during the analysis of a modern condition of use of the earths of establishments and the enterprises of NAAS is presented and generalized. Ways to solve the identified problems on the example of land institutions and enterprises of NAAS, which are the need for land inventory, as the main tools for land management, as well as consistency of information SLC, SRRR, return of illegally allotted land to third parties. Key words: land use NAAS, State Land Cadastre, State Register of Real Property Rights, title documents.